![\huge (i)\dfrac{3 + \sqrt{2} }{3 - \sqrt{2} } = a + b \sqrt{2} \huge (i)\dfrac{3 + \sqrt{2} }{3 - \sqrt{2} } = a + b \sqrt{2}](https://tex.z-dn.net/?f=+%5Chuge+%28i%29%5Cdfrac%7B3+%2B++%5Csqrt%7B2%7D+%7D%7B3+-++%5Csqrt%7B2%7D+%7D++%3D+a++%2B+b+%5Csqrt%7B2%7D+)
Please solve the question...
No spam plz...
#BrainlyStar #EmergerModerator
@Somya2563
Answers
Answered by
7
Do Rationalization,
(3+√2)(3+√2)/(3-√2)(3+√2)= a+b√2
9+6√2+2 / 9-2 = a+b√2
11+6√2 / 7 = a+b √2
11/7 + 6√2/7 = a+b√2
we can also write it as 11/7+6/7×√2 = a+b√2
So 11/7+6/7×√2 is in the form of a+b√2
So, we got the answer as
a=11/7 and b= 6/7
Answer : a=11/7 and b= 6/7
Answered by
2
Answer:
(3+√2)(3+√2)/(3-√2)(3+√2)= a+b√2
9+6√2+2 / 9-2 = a+b√2
11+6√2 / 7 = a+b √2
11/7 + 6√2/7 = a+b√2
we can also write it as 11/7+6/7×√2 = a+b√2
So 11/7+6/7×√2 is in the form of a+b√2
Answer Is
a=11/7 and b= 6/7
Step-by-step explanation:
please mark me as a brain list
Similar questions